Pandemic process in children (Annals of Medical Research, 2023)
Aim: When compared to adults, it is seen that the COVID-19 disease in children has a milder course. However, considering that there are cases with severe course and even death, it is aimed to analyze the COVID-19 PCR positivity in children according to age and gender.Materials and Methods: Between March 7, 2020 and August 18, 2021, throat and nose swab samples from children with clinical complaints or a history of contact were evaluated by reverse transcriptase polymerase chain reaction (RT-PCR) and the distribution of positive children by age and gender classified.Results: The PCR test was positive in 3,181 (30.74%) out of 10,342 children, the highest positivity rate was 33.52% in male and in the 15-18 age range, while this rate was 36.77% in female in the 15-18 age range.Conclusion: In this study, it was determined that the prevalence of the COVID19 pandemic, which affected the whole world, in childhood age groups was highest in male and between the ages of 15-18.
Keywords: Age; Pandemi; PCR; Pediatrics